Dénoncer les féminicides des femmes autochtones aux États-Unis et au Canada La bande dessinée Deer Woman d’Elizabeth LaPensée, une super-héroïne autochtone éco-féministe ? - Bonadè, Sophie; Hamus-Vallée, Réjane; Journée-Duez, Aurélie (Genre en séries, 2019)
À travers l’analyse de la bande dessinée Deer Woman créée en 2015 par Elizabeth LaPensée (Anishinaabe, Canada), notre article a pour objectif principal d’interroger la notion de « super-héroïne » à l’aune de représentations autochtones engagées. Il s’agit de voir en quoi cette revitalisation du mythe traditionnel de la Femme Cerf (Deer Woman) interroge l’identité en termes de sexe et de genre, la culture et la place des femmes autochtones, en prenant une position radicale face au problème sociétal des féminicides en Amérique du Nord. Nous postulons que la figure de Deer Woman peut aussi être vue aujourd’hui comme une allégorie mettant en garde contre la domination masculine sur les femmes et sur toutes autres formes de vie. Tout d’abord, nous étudierons les caractéristiques formelles de Deer Woman et les mythes fondateurs autochtones qui en sont à l’origine. Nous montrerons ensuite en quoi cette super-héroïne dont les pouvoirs apparaissent après qu’elle a été sexuellement agressée, tend à dénoncer et lutter contre les féminicides touchant les femmes autochtones. Enfin, nous nous demanderons comment cette bande dessinée pourrait laisser entrevoir l’émergence d’une super-héroïne autochtone éco-féministe.
Keywords: amérique du nord; amériques; approches et analyses; arts; bande-dessinée; cours; discipline; environnement; féminicide; féminisme autochtone; féminisme pop; histoire et politique; justice sociale; militance; pol4105; premier cycle; racisme; régions géographiques; sexisme; super-héroïnes; système colonial; systèmes d'oppressions; thématiques; violences; écoféminisme; études littéraires

Women and Ecosystems - Frontlines Amazon (Amazon Frontlines, 2019)
Keywords: amérique latine; amériques; approches et analyses; environnement; féminisme autochtone; inégalités; militance; ressource en ligne; régions géographiques; systèmes d'oppressions; thématiques; écoféminisme

The Routledge companion to feminist philosophy - Garry, Ann; Khader, Serene J.; Stone, Alison (Routledge, 2017)
"The Routledge Companion to Feminist Philosophy is an outstanding guide and reference source to the key topics, subjects, thinkers, and debates in feminist philosophy. Fifty-six chapters, written by an international team of contributors specifically for the Companion, are organized into five sections: (1) Engaging the Past; (2) Mind, Body, and World; (3) Knowledge, Language, and Science; (4) Intersections; (5) Ethics, Politics, and Aesthetics. The volume provides a mutually enriching representation of the several philosophical traditions that contribute to feminist philosophy. It also foregrounds issues of global concern and scope; shows how feminist theory meshes with rich theoretical approaches that start from transgender identities, race and ethnicity, sexuality, disabilities, and other axes of identity and oppression; and highlights the interdisciplinarity of feminist philosophy and the ways that it both critiques and contributes to the whole range of subfields within philosophy."–The publisher.
Le chapitre 22 de Miranda Fricker et Katharine Jenkins, “Epistemic injustice, ignorance, and trans experiences” a été donné en lecture au cours FEM9000.
Keywords: afro-féminisme; approches et analyses; autonomie; bioéthique; care; cours; cycles supérieurs; discipline; environnement; esthétique; fem9000; féminisme africain; féminisme autochtone; féminisme décolonial; féminismes noirs; identité; injustices épistémiques; intersectionnalité; justice sociale; matérialité; objectivité; outils; ouvrages de références; philosophie; philosophie féministe; phénoménologie; politique de genre; queer; rationnalité; religion; sciences humaines; subjectivité; thématiques; théorie du contrat social; transféminisme; écologie; éthique; éthique du care; études critiques de la race; études critiques du handicap

Deer Woman: an anthology - LaPensée, Elizabeth; Alvitre, Weshoyot; Stonefish, Patty; Vasquez, Allie; Naragon, Rebecca; Thunder, Jonathan; Native Realities (Firm); Arming Sisters (Organization) (Native Realities, LLC, 2017)
Based on the true stories of Indigenous women throughout the world, Deer Woman: An Anthology is an extension of the Deer Woman: A Vignette, comic book that itself is a powerful expression and weaves the stories of Deer Woman into a modern narrative of the struggles of Indigenous women in North America. This anthology features the work of more than a dozen Native women sharing stories of survival, empowerment, and healing. Edited by Elizabeth LaPensée and Weshoyot Alvitre and featuring the work of: Patty Stonefish, Allie Vasquez, Mia Casesa, Darcie Little Badger, Tara Ogaick, Kimberly Robertson, Barbara Kenmille, Maria Wolf Lopez, Tatum Bowie, Jackie Fawn, Rebecca Roanhorse, Carolyn Dunn, Nashoba Dunn-Anderson, and more, this anthology is an important addition to the current conversation about violence against women, especially Native women.-from publisher's website.
Section: 1 volume (unpaged) : chiefly illustrations (some color) ; 26 cm
Keywords: amérique du nord; amériques; approches et analyses; arts; arts visuels et médiatiques; bande-dessinée; care; cours; discipline; environnement; féminisme autochtone; histoire et politique; intersectionnalité; militance; pol4105; premier cycle; racisme; régions géographiques; sexisme; sofia; système colonial; systèmes d'oppressions; thématiques; violences; écoféminisme; études littéraires

Living on the land: indigenous women's understanding of place - Altamirano-Jiménez, Isabel; Kermoal, Nathalie J.; Horn-Miller, Kahente (AU Press, 2016)
From a variety of methodological perspectives, contributors to Living on the Land explore the nature and scope of Indigenous women's knowledge, its rootedness in relationships, both human and spiritual, and its inseparability from land and landscape.
Le texte de Horn Miller, Kahente (2016). Distortion and Healing: Finding Balance and a ‘Good Mind’ through the rearticulation of Sky Woman’s Journey, a été donné en lecture au cours POL4105.
Keywords: amériques; approches et analyses; canada; cours; cree; discipline; environnement; féminisme autochtone; histoire; métis; naskapi; nicaragua; pol4105; premier cycle; ressource en ligne; régions géographiques; sciences humaines; thématiques; études autochtones; île de la tortue

Amun: nouvelles - Jean, Michel (Stanké, une société de Québecor média, 2016)
« Dans la langue innue, amun signifie « rassemblement ». Sous la direction de Michel Jean, écrivain et journaliste innu, ce collectif brûlant d'actualité réunit des auteurs autochtones de divers horizons, de différentes nations et générations. Leurs nouvelles, variées, reflètent non seulement l'histoire et les traditions, mais aussi la réalité des Premières Nations au Québec et au Canada. Offrant à lire les points de vue d'artistes de renom, ce livre est le théâtre d'un rassemblement qui ne se fait que trop rarement. »–Quatrième de couverture.
Les nouvelles de Fontaine, Natacha Kanapé, 2016. « J’ai brûlé toutes les lettres de mon prénom » et de Cousineau-Mollen, Maya, 2016. « Mitatamun (Regret) » ont été données en lecture au cours SEX2283
Keywords: amériques; appartenance; approches et analyses; arts; canada; cours; discipline; environnement; féminisme autochtone; littérature; littérature autochtone; pensionnats; premier cycle; premières nations; québec; racisme; régions géographiques; sex2283; spiritualité; système colonial; systèmes d'oppressions; thématiques; violences; études littéraires

CIRFF 2015 - Soirée d'ouverture et plenière d'ouverture avec Natasha Kanapé Fontaine (2015)
7e Congrès international des recherches féministes dans la francophonie (CIRFF2015) Plénière d’ouverture sous le thème Penser Créer Agir avec : - Natasha Kanapé Fontaine, poète et slameuse. Lundi 24 août, salle Marie-Gérin-Lajoie, UQAM.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; antiféminisme; antiracisme; approches et analyses; environnement; féminisme autochtone; histoire et politique; identités; identités culturelles; justice sociale; maternité; mohawk; poésie; périodes historiques; québec; ressource en ligne; régions géographiques; terre nouricière; territoire; thématiques; écriture des femmes*

Land as pedagogy: Nishnaabeg intelligence and rebellious transformation - Simpson, Leanne Betasamosake (Decolonization: Indigeneity, Education & Society, 2014)
A resurgence of Indigenous political cultures, governances and nation-building requires generations of Indigenous peoples to grow up intimately and strongly connected to our homelands, immersed in our languages and spiritualities, and embodying our traditions of agency, leadership, decision-making and diplomacy. This requires a radical break from state education systems – systems that are primarily designed to produce communities of individuals willing to uphold settler colonialism. This paper uses Nishnaabeg stories to advocate for a reclamation of land as pedagogy, both as process and context for Nishnaabeg intelligence, in order to nurture a generation of Indigenous peoples that have the skills, knowledge and values to rebuild our nation according to the word views and values of Nishnaabeg culture.
Number: 3
Keywords: amériques; approches et analyses; canada; cours; discipline; environnement; féminisme autochtone; histoire et politique; nishnaabeg; pol4105; premier cycle; premières nations; pédagogie; pédagogie nishnaabeg; régions géographiques; résistance; résurgence; savoirs autochtones; sciences de l'éducation; sciences humaines; sociologie; système colonial; systèmes d'oppressions; systèmes éducatifs; territoire nishnaabeg; thématiques; éducation par le territoire

Idle No More: identité autochtone actuelle, solidarité et justice sociale : Entrevue avec Melissa Mollen Dupuis et Widia Larivière - Gentelet, Karine (Nouvelles pratiques sociales, 2014)
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; canada; cours; discipline; droit; droits des femmes*; environnement; féminisme autochtone; militance; pol4105; premier cycle; périodes historiques; québec; ressource en ligne; régions géographiques; science politique et droit; thématiques

Plan Nord - Où sont les femmes autochtones ? - Arnaud, Aurélie (Recherches amérindiennes au Québec, 2011)
Parmi les sujets absents du débat sur les impacts et les conséquences du Plan Nord se trouvent, invisibles, les femmes autochtones. Celles qui constituent plus de 50 % de la population autochtone dans le Nord sont les moins écoutées, les moins consultées, les plus vulnérables. La question est absente et il y a peu de données disponibles quant à l’impact des activités minières ou des chantiers hydroélectriques sur la condition des femmes. Or, l’expérience de Femmes autochtones du Québec révèle que ce type de développement a souvent des incidences négatives sur la situation des femmes autochtones dans les communautés en exacerbant les préjugés, les violences et les inégalités. Pour poser la réalité des femmes autochtones dans et hors réserve, il faut préciser qu’en 2001, les femmes autochtones enregistraient un taux de monoparentalité deux fois plus élevé que celui des femmes non autochtones (19 % contre 8 %). Les nombreuses familles dirigées par des femmes autochtones sont donc plus dépendantes de l’aide sociale que les hommes autochtones le sont.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; canada; care; cours; discipline; environnement; féminisme autochtone; histoire et politique; intersectionnalité; inégalités; justice sociale; pol4105; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; sciences sociales; sexisme; système colonial; systèmes d'oppressions; thématiques; violences

Indigenous women and feminism: politics, activism, culture - Suzack, Cheryl; Huhndorf, Shari M.; Perreault, Jeanne; Barman, Jean (UBC Press, 2010)
"Can the specific concerns of Indigenous women be addressed within current mainstream feminist and post-colonial discussions? Indigenous Women and Feminism: Politics, Activism, Culture proposes that a dynamic new line of inquiry – Indigenous feminism – is necessary to truly engage with the crucial issues of cultural identity, nationalism, and decolonization particular to Indigenous contexts. Through the lenses of politics, activism, and culture, this wide-ranging collection examines the historical roles of Indigenous women, their intellectual and activist work, and the relevance of contemporary literature, art, and performance for an emerging Indigenous feminist project. The questions at the heart of these essays – What is at stake in conceptualizing Indigenous feminism? How does feminism relate to Indigenous claims to land and sovereignty? What lessons can we learn from the past? How do Indigenous women engage ongoing violence and social and political marginalization? – cross disciplinary, national, academic, and activist boundaries to explore in depth the unique political and social positions of Indigenous women."–Page 4 de la couverture."A vital and sophisticated discussion that will change the way we think about modern feminism, Indigenous Women and Feminism will be invaluable to scholars, activists, artists, community organizers, and those concerned with Indigenous and feminist issues at home and abroad."– Résumé de l'éditeur.
Le texte de Tsosie, Rebecca (2011). Native Women and Leadership: An Ethics of Culture and Relationship a été donné en lecture au cours POL4105.
Keywords: activisme; approches et analyses; arts; cours; discipline; environnement; féminisme autochtone; féminisme décolonial; histoire et politique; militance; pol4105; premier cycle; premières nations; système colonial; systèmes d'oppressions; territoire; thématiques; études autochtones; études féministes; études littéraires

Bâtons à message = Tshissinuatshitakana - Bacon, Joséphine (Mémoire d'encrier, 2009)
"Cet ouvrage bilingue (français et innu-aimun) est une invitation au dialogue. Bâtons à message fait référence à un ensemble de repères qui permettent aux nomades de s’orienter à l’intérieur des terres et de retrouver leur voie/voix. Également poétique de la relation, l’ouvrage est fondé sur l’entraide, la solidarité et le partage, nécessaires à la survie du peuple innu. La poésie de Joséphine Bacon, simple et belle, est hommage au territoire, aux ancêtres et à la langue innu-aimun. Cette poésie-témoignage recoupe l’histoire dans ses zones les plus inédites. Une vision cosmogonique qui nous plonge dans l’intensité de la parole des aînés: l’itinéraire des porteurs de rêves et de visions, les horizons des femmes guides, le courage des hommes chasseurs, les enfants garants de la continuité du voyage et les arbres, infatigables témoins de la route."– Site de l'éditeur.
Section: 141 pages ; 19 cm
Keywords: amériques; approches et analyses; arts; canada; cours; discipline; environnement; féminisme autochtone; lit3495; poésie; premier cycle; québec; régions géographiques; thématiques; écriture des femmes*; études littéraires

L'association des femmes inuites du Nunavik Saturviit : porteuses d'espoir et de paix - Koperqualuk, Lisa Q. (2008)
La revue est disponible gratuitement à cette adresse: https://numerique.banq.qc.ca/patrimoine/details/52327/21235?docref=7WwAmupy7jFapVusT6o59A
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; canada; cours; discipline; environnement; famille; féminisme autochtone; inégalités; maternité; nunavik; pol4105; premier cycle; périodes historiques; régions géographiques; science politique; science politique et droit; sexisme; système colonial; systèmes d'oppressions; thématiques; travail; violences

Anishnaabe-Kwe, traditional knowledge, and water protection - McGregor, Deborah (Canadian Woman Studies, 2008)
26CANADIAN WOMAN STUDIES/LES CAHIERS DE LA FEMMEDans cet article, l’auteure partage ses expériences de travail sur les questions environnementales, particulièrement sur celles qui concernent l’eau. Comme mère, comme membre d’un clan, comme membre des Premières Nations et comme professeure, l’auteure se sent responsable du partage de ses connaissances. Cette réflexion est basée sur son travail avec les aînées et les tenants du savoir traditionnel en Ontario, surtout de celui qui se rapporte à l’eau. L’information part de deux projets majeurs dans lesquels elle a été impliquée.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; canada; cours; discipline; droit; droit de l'environnement; eau; environnement; féminisme autochtone; ontario; point de vue situé; pol4105; premier cycle; pédagogie; périodes historiques; régions géographiques; science politique et droit; sciences de l'éducation; thématiques; transmissions; écoféminisme; écoféminisme amérindien

Itinéraires d'égalités. Trajectoires des femmes autochtones du Québec et du Canada - Levesque, Carole; Labrecque, Marie France (2007)
À l’occasion du 30e anniversaire de l’Association des Femmes autochtones du Québec, ces actes de colloque proposent de revoir le parcours des femmes autochtones dans leurs luttes pour l’égalité et la justice sociale.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; canada; cours; discipline; droits des femmes*; environnement; féminisme autochtone; histoire et politique; inégalités; justice sociale; mexique; militance; pol4105; premier cycle; pédagogie; périodes historiques; québec; ressource en ligne; régions géographiques; sciences humaines; sciences sociales; système colonial; systèmes d'oppressions; thématiques; violences; études autochtones

Suzanne MacKenzie Memorial Lecture conceptually unclad: feminist geography and Aboriginal peoples * - Peters, Evelyn J. (The Canadian Geographer, 2004)
This paper argues that feminist geography can provide some useful lessons in an attempt to increase Aboriginal peoples' representation in geography. It asks the question: How can we use the example of feminist geography to think about a geography that is more inclusive of Aboriginal people? The paper focuses on the issues of content in teaching, drawing on examples from urban and social geography, and on methodological challenges, especially the issue of reflexivity. Feminist geographer Suzanne Mackenzie argued that an emerging feminist geography left the discipline ‘conceptually unclad’, challenging scholars to consider new theoretical frameworks and new perspectives. I argue that emphasising the geographies of Aboriginal people also enriches geography, including feminist geography.
Keywords: 2000 à aujourd'hui; 2000-2009; approches et analyses; cours; discipline; démographie; environnement; féminisme autochtone; géographie; géographie féministe; géographie urbaine; histoire et politique; méthodologie; pol4105; premier cycle; périodes historiques; sciences humaines; thématiques

Feminism and the body - Schiebinger, Londa (Oxford University Press, 2000)
This exciting new Handbook offers a comprehensive overview of the contemporary state of the field. The editors’ introduction and forty-five essays cover feminist critical engagements with philosophy and adjacent scholarly fields, as well as feminist approaches to current debates and crises across the world. Authors cover topics ranging from the ways in which feminist philosophy attends to other systems of oppression, and the gendered, racialized, and classed assumptions embedded in philosophical concepts, to feminist perspectives on prominent subfields of philosophy. The first section contains chapters that explore feminist philosophical engagement with mainstream and marginalized histories and traditions, while the second section parses feminist philosophy’s contributions to with numerous philosophical subfields, for example metaphysics and bioethics. A third section explores what feminist philosophy can illuminate about crucial moral and political issues of identity, gender, the body, autonomy, prisons, among numerous others. The Handbook concludes with the field’s engagement with other theories and movements, including trans studies, queer theory, critical race, theory, postcolonial theory, and decolonial theory. The volume provides a rigorous but accessible resource for students and scholars who are interested in feminist philosophy, and how feminist philosophers situate their work in relation to the philosophical mainstream and other disciplines. Above all it aims to showcase the rich diversity of subject matter, approach, and method among feminist philosophers.
Section: IX, 500 pages : illustrations ; 22 cm
Keywords: LGBTQIA2+; afro-féminisme; approches et analyses; corps; cours; discipline; environnement; féminisme autochtone; féminisme décolonial; histoire et politique; identités LGBTQIA2+; incontournable; intersectionnalité; lit4700; oui; philosophie; postmodernisme; premier cycle; queer; ressource en ligne; sciences humaines; thématiques; transféminisme